CENTER FOR INTERPRETATION: ARCHITECTURAL ANALYSIS AND DESIGN (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
The article is dedicated to studying architectural aspects in the design of interpretation centers – special spaces intended to reveal and explain cultural, historical, and natural heritage. Key factors influencing the success of such projects are analyzed: location selection, interior and exterior design, and the application of innovative technologies. The research is based on an analysis of scientific literature and the study of successful cases. Special attention is given to integrating architecture with the landscape, using virtual and augmented reality, creating flexible spaces, and ensuring ecological sustainability. The research results demonstrate that successful interpretation centers are repositories of information and inspiring spaces that harmoniously blend into the surrounding environment. A comprehensive approach to design, taking into account both the functional and emotional needs of visitors, allows for the creation of unique architectural solutions that contribute to the preservation of cultural and natural heritage for many years to come.